twee voorbeelden

Voorbeeld 1

$
\eqalign{
  & 3\sin (x) - 2\sin ^2 (x) = 1  \cr
  & 2\sin ^2 (x) - 3\sin (x) + 1 = 0  \cr
  & (\sin (x) - 1)(2\sin (x) - 1) = 0  \cr
  & \sin (x) = 1 \vee 2\sin (x) = 1  \cr
  & \sin (x) = 1 \vee \sin (x) = \frac{1}
{2}  \cr
  & x = \frac{1}
{2}\pi  + k \cdot 2\pi  \vee x = \frac{1}
{6}\pi  + k \cdot 2\pi  \vee x = \frac{5}
{6}\pi  + k \cdot 2\pi  \cr}
$

Voorbeeld 2

$
\eqalign{
  & \frac{1}
{7}\sin \left( {x - \frac{1}
{3}\pi } \right) \cdot \cos ^2 \left( x \right) = 0  \cr
  & \sin \left( {x - \frac{1}
{3}\pi } \right) = 0 \vee \cos ^2 \left( x \right) = 0  \cr
  & x - \frac{1}
{3}\pi  = k \cdot \pi  \vee x = \frac{1}
{2}\pi  + k \cdot \pi   \cr
  & x = \frac{1}
{3}\pi  + k \cdot \pi  \vee x = \frac{1}
{2}\pi  + k \cdot \pi  \cr}
$

©2004-2021 W.v.Ravenstein